Probing active-sterile neutrino transition magnetic moment on coherent elastic solar neutrino-nucleus scattering - M. Demirci; M. F. Mustamin (European Physical Journal C: Particles and Fields)
Abstract In the presence of a transition magnetic moment between active and sterile neutrinos, sterile neutrinos could be produced by neutrino beams electromagnetically upscattering on nuclei. We study the active-sterile neutrino transition magnetic moment through this upscattering in the coherent elastic neutrino-nucleus scattering process induced by solar neutrinos. We place new limits on the transition magnetic moment-sterile neutrino mass plane using the latest data from the CDEX-10 experiment. We also provide projected sensitivities for future measurements. We observe that the projected sensitivities could cover some regions of the parameter space which were previously unexplored for the sterile neutrino mass up to $$\sim 10$$ ∼ 10 MeV.